Sierraperla Jewett 1954 (Plecoptera: Peltoperlidae), distribution, egg morphology and description of a new species - Stark, Bill P. (Illiesia, 2015)
The genus Sierraperla Jewett is reviewed and a new species, S. tolowa is recognized. Data supporting recognition of the new species include scanning electron microscopy of egg chorion, adult external terminalia, morphology of internal male genitalia, adult pigment patterns, and DNA barcodes (cytochrome c oxidase I; COI).
Keywords: entomology; stoneflies; Perlodidae; Plecoptera; egg morphology; Sierraperla; scanning electron microscopy; COI gene; cytochrome c oxidase I; new species; DNA barcodes